Manipulative auction design - Philippe Jehiel (Theoretical Economics, 2011)
This paper considers an auction design framework in which bidders get partial feedback about the distribution of bids submitted in earlier auctions: either bidders are asymmetric but past bids are disclosed in an anonymous way or several auction formats are being used and the distribution of bids but not the associated formats are disclosed. I employ the analogy-based expectation equilibrium (Jehiel, 2005) to model such situations. First-price auction in which past bids are disclosed in an anonymous way generates more revenues than the second-price auction while achieving an efficient outcome in the asymmetric private values two-bidder case with independent distributions. Besides, by using several auction formats with coarse feedback a designer can always extract more revenues than in Myerson's optimal auction, and yet less revenues than in the full information case whenever bidders enjoy ex-post quitting rights and the assignment and payment rules are monotonic in bids. These results suggest an important role of feedback disclosure as a novel instrument in mechanism design.
Keywords: C72; D82; D84; 330; Auction design; feedback equilibrium; manipulation